Some implications of non-reporting and self-reporting of crime on criminal justice research - Adams, Reed (American journal of criminal justice, 1975)
There are reasonable grounds for assuming that unreported crime is extensive. Inasmuch as questionnaires are the major source of data for self-reported crime and delinquency and Clark and Tifft have seriously challenged the validity of this data source, it seems these areas lack a valid and unequivocal basis for assessing theory. It seems rather pointless to pursue etiological studies until new, valid, and reliable sources of data are available for theory construction and testing. The contention that interdisciplinary research is needed in Criminology is strengthened by the Clark and Tifft study, which offers an instance of fruitful interdisciplinary collaboration. Other recognized examples of significant interdisciplinary effort include the works of Pasmanick, et.al. ,^23 Srole, et. al. ,^24 and Lindner, et. al. ^25 Students of crime and delinquency must break through the parochialism of unitary and doctrinaire commitment to their own disciplines. In particular, sociologists must learn increasingly to utilize and embrace, at least on the micro-level, the potentials offered by other sciences, especially the life sciences. An alternative to this proposal would be a largescale consecutive birth study; then, perhaps in a quarter of a century, we might have the data necessary to formulate tentative etiological conclusions.